The Effect of Nutrient Composition on the Growth of Kale Plants in Hydroponic Systems - Soelistianto, Farida Arinie; Yohan, Yohan; Suparwata, Dewa Oka; Marjan, M; Amaludin, Moh. Baitullah (West Science Agro, 2025)
This study reviews the impact of nutritional composition on the growth of kale (Brassica oleracea var. acephala) in hydroponic systems, synthesizing findings from 15 Scopus-indexed studies. The analysis highlights the critical roles of macronutrients (nitrogen, phosphorus, potassium) and micronutrients (iron, magnesium, zinc) in optimizing plant growth, yield, and quality. Additionally, it examines the importance of nutrient solution management, including pH, electrical conductivity, and nutrient concentration, for efficient nutrient uptake. Innovative practices such as organic additives and advanced monitoring systems are also discussed for their potential to enhance productivity and sustainability. The review identifies gaps in existing research, particularly in standardizing nutrient formulations and assessing the long-term impact on nutritional quality. These findings provide actionable insights for researchers and practitioners aiming to advance hydroponic kale cultivation.